Association between Glycated Hemoglobin and Lipid Proﬁle in Type 2 Diabetes Mellitus Patients Attending Tertiary Care Hospital: A Cross Sectional Study - Mahesh Raj Ghimire; Sundar Pandey; Deepak Aryal; Pooja Shah; Monica Thapa; Yogesh Pandey; Aliza Aryal; Pooja Belbase; Rahul Budhathoki (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Glycated haemoglobin levels are routinely measured in type 2 diabetes mellitus to monitor their glycaemic control. Lipid disorder in diabetes is common issues either independently or in association with type 2 Diabetes mellitus. We aim to establish the association between Glycated haemoglobin and lipid proﬁle in type 2 diabetes mellitus patients attending our centre. MATERIAL AND METHODS This is hospital based cross-sectional study conducted on 161 patients conducted in out-patient department of internal medicine and from 10/02/2079 to 20/04/079 at Devdaha Medical College and Research Institute (DMCRI). Patients were enrolled after taking informed consent fulﬁlling inclusion and exclusion criterias. Data were entered on Microsoft Excel 2010 and analyzed using SPSS v25. RESULTS Among 161 Participants, male to female ratio was almost 1:1, with mean age of diabetes of male and female was 58.1 ± 11.2 standard deviation (SD) and 56.7 ± 10.4 SD, with 13.04% were alcohol consumer; 1.86% were smokers; 57.76% of them had high blood pressure; (29.19%) had known dyslipidaemia and 11.18% had hypothyroidism. While comparing controlled (HBA1c<7%) with uncontrolled (HBA1c ≥7%) glycated hemoglobin and level of different components of lipid proﬁle like total cholesterol, triglyceride, LDL- cholesterol and HDL-cholesterol, there is statistical correlation [χ²=4.67; df=1; p=0.031] between only high triglyceride level and uncontrolled type 2 diabetes. CONCLUSION High value of glycated hemoglobin not only measures uncontrolled type 2 diabetes but can also be considered for high lipid disorder biomarker. Early detection of high glycated hemoglobin could prevent complications related with diabetes independently or in combine with dyslipidemia.